Benefits of electrifying app-taxi fleet – A simulation on trip data from New Delhi. (January 2022) - Rajagopal, Deepak; Sawant, Viraj; Bauer, Gordon S.; Phadke, Amol A.
Highlights: On-demand taxi fleets of electric vehicles will be cheaper than Diesel and CNG powered vehicles. Transitioning to fully electric fleet will yield massive air quality benefits. Environmental footprint of electricity remains an area of concern while considering lifecycle emissions of non-greenhouse gas air pollutants. Modeling for electrification in developing countries needs to recognize local constraints. Abstract: Battery electric vehicles (BEVs) appear integral to improving urban air quality, especially in less-wealthier countries whose cities rank amongst the most polluted and fastest growing. But despite steep declines in battery prices and generous subsidies, BEV adoption in such countries is weak. Here, the tremendous growth of app-taxi and retail delivery vehicles presents a massive new opportunity. Since they register several-fold greater utilization relative to the average pure private-use vehicle, electrifying such vehicles could deliver rapid financial payback and much greater economic and pollution benefits. A general framework for spatially-detailed estimation of charging infrastructure, and the economic and environmental benefits of commercial fleet electrification was developed and applied to a dataset comprising ∼ 730, 000 app-taxi trips spanning ∼ 15 million kilometers (km) in Delhi, India, which shows: i) ∼ 23000 BEVs with 200 km range and a network of 3000 50 kilo-Watt chargers could satisfy 100% of Delhi's daily app-taxi demand, and relative to a compressed natural gas (diesel) fleet eliminate 180 (7 0 0) and 0.14 (70) metric tonnes of vehicle tail-pipe NOX and particulate matter emissions respectively annually and reduce lifecycle greenhouse gas emissions by 15% (27%) per km. Cost savings are sensitive to retail BEV price and government subsidies, which are not indicative of future prices given the infancy of BEV industry. Under current prices and subsidies in India, BEVs reduce levelized cost per km 21% and 37% relative to CNG and Diesel vehicles respectively. Electrification of taxi fleets increases aggregate electricity consumption 2% with insignificant increase during daily peak demand hours. Therefore, ambitious zero emissions vehicle targets for commercial light duty vehicle fleets appear environmentally, economically and socially sound.